The effect of pH on the extraction yield of camel hides gelatin and its potential application in Halal industry - Jaswir, Irwandi; Mirghani, Mohamed Elwathig Saeed; Aboulala, Slimane (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Gelatin is an animal protein which is obtained by partial hydrolysis of the collagen. It is widely used in food industry, pharmaceutical, and cosmetic products too. Since its origin is from an animal, revealed questions of its Halal status. Camel Hide as new sources of gelatin, yet, it did not explore as much as porcine and bovine gelatin. The present work aimed to determine the optimum conditions for extraction parameters for Camel Hide Gelatin (CHG). One Factor At Time (OFAT) was used as a model of Design Of Expert (DOE), in which the acidic pH (2.5/3.5/4.5) was optimized with fixed two parameters: temperature and time of extraction for six steps of extraction, (45°C to 95°C / 5h to 13h). The yield of extracted gelatin was chosen as the response. The results showed the highest total yield for all 6 steps of extraction for pH 3.5 was at 18.90 % (wet weight).